Model Teams Games Tournament - Bukhari (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The Teams Games Tournaments model is one model that is easy to apply in learning because it involves the activities of all students and the presence of elements of the game which of course every student really likes the game and also the award that will be given by the teacher based on the highest score that will be obtained by students. The Teams Games Tournaments model is part of the cooperative learning model that can activate students as a whole. Cooperative learning is a learning model in which students learn and work in small groups collaboratively with 4-6 members with a heterogeneous group structure as well as awards that will be given by the teacher based on the highest score that will be obtained by students. The teacher's role in this model is to present the material and students work in their respective groups. The learning model also serves as a guide for learning designers and teachers in planning activities in the teaching and learning process.